Bacterial products in donor airways prevent the induction of lung transplant tolerance. Issue 1 (5th September 2020) - Tanaka, Satona; Gauthier, Jason M.; Terada, Yuriko; Takahashi, Tsuyoshi; Li, Wenjun; Hashimoto, Kohei; Higashikubo, Ryuji; Hachem, Ramsey R.; Bharat, Ankit; Ritter, Jon H.; Nava, Ruben G.; Puri, Varun; et al.
Abstract : Although postoperative bacterial infections can trigger rejection of pulmonary allografts, the impact of bacterial colonization of donor grafts on alloimmune responses to transplanted lungs remains unknown. Here, we tested the hypothesis that bacterial products present within donor grafts at the time of implantation promote lung allograft rejection. Administration of the toll‐like receptor 2 (TLR2) agonist Pam3 Cys4 to Balb/c wild‐type grafts triggered acute cellular rejection after transplantation into B6 wild‐type recipients that received perioperative costimulatory blockade. Pam3 Cys4 ‐triggered rejection was associated with an expansion of CD8 + T lymphocytes and CD11c + CD11b hi MHC (major histocompatibility complex) class II + antigen‐presenting cells within the transplanted lungs. Rejection was prevented when lungs were transplanted into TLR2‐deficient recipients but not when MyD88‐deficient donors were used. Adoptive transfer of B6 wild‐type monocytes, but not T cells, following transplantation into B6 TLR2‐deficient recipients restored the ability of Pam3 Cys4 to trigger acute cellular rejection. Thus, we have demonstrated that activation of TLR2 by a bacterial lipopeptide within the donor airways prevents the induction of lung allograft tolerance through a process mediated by recipient‐derived monocytes. Our work suggests that donor lungs harboring bacteria may precipitate an inflammatory response that can facilitate allograft rejection. Abstract : Bacterial products within donor airways trigger rejection of lung allografts through activation of innate immune signaling in recipient cells.